An Endoscopic Endonasal Approach for Early-Stage Olfactory Neuroblastoma: An Evaluation of 2 Cases with Minireview of Literature - Hidenori Yokoi; Satoru Kodama; Yasunao Kogashiwa; Yuma Matsumoto; Yasuo Ohkura; Takayuki Nakagawa; Naoyuki Kohno (Case Reports in Otolaryngology)
We describe the clinical findings in two patients with pathologically diagnosed olfactory neuroblastoma (ONB) of the sinonasal area and the surgical methods used for its treatment. Using an endoscopic endonasal approach (EEA) without dura resection, along with radiotherapy, we successfully treated ONB at the Kadish stage A. One of our patients, however, experienced tumor recurrence 24 years after open surgery with radiotherapy that was conducted at another hospital. This patient was no longer eligible for radiotherapy, and the tumor was therefore resected with dura resection using an EEA combined with duraplasty. The dura resection with duraplasty using fascia lata and a pedicled nasal septal flap was minimally invasive. As with surgery without duraplasty, a postoperative computed tomography (CT) examination revealed that EEA with duraplasty led to quick improvement of the postoperative inflammatory response as well as pneumocranium. Here, we investigated whether to modify the method of surgery depending upon the primary site of early-stage ONB. We suggest that, in early-stage ONB, an endoscopic endonasal approach is an effective and less invasive method. It is also advisable to perform dura mater resection of the lesion site despite the absence of obvious intracranial invasions in image findings.